2003
DOI: 10.1023/a:1024856207478
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of heavy metals and related trace elements in some Ethiopian rift-valley lakes and their in-flows

Abstract: Concentrations of heavy metals commonly known to impact the environment and other related trace elements were quantified in the water bodies of nine Ethiopian rift-valley lakes and six rivers ( their inflows) as well as in effluents from two factories. In about half of the samples the concentrations of As was 10 - 700 mug l(-1) and Se, ranged from 10 to 28 mug l(-1), were much higher than the maximum permissible level (MPL) according to international standards for drinking water. Mercury ( Hg) was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 16 publications
1
24
1
1
Order By: Relevance
“…In all sampled points the Cr, Cd, Ni and Pb were non-detectable; these make the lake water suitable for aquatic life like fish. The study value of heavy metals results were agrees with the former investigation of Lake Hawassa done by Zinabu & Pearce (2003). Based on the result obtained (heavy metals found) in the lake water was suitable for drinking, irrigation and aquatic uses (USEPA, 1998;WHO, 1984;.…”
Section: Heavy Metals Analysis For the Intended Usessupporting
confidence: 89%
“…In all sampled points the Cr, Cd, Ni and Pb were non-detectable; these make the lake water suitable for aquatic life like fish. The study value of heavy metals results were agrees with the former investigation of Lake Hawassa done by Zinabu & Pearce (2003). Based on the result obtained (heavy metals found) in the lake water was suitable for drinking, irrigation and aquatic uses (USEPA, 1998;WHO, 1984;.…”
Section: Heavy Metals Analysis For the Intended Usessupporting
confidence: 89%
“…The lake is one of the Ethiopian rift valley lakes and has a surface area of about 90 km 2 [20]. The maximum and mean depths of the lake are 22 m and 11 m, respectively [19].…”
Section: Site Descriptionsmentioning
confidence: 99%
“…Concern over the health hazards of Hg has prompted much global research on the geochemistry of this element. SigniWcant data on the distribution of Hg in the EARV exist only for the lakes (e.g., Bongonso et al 1996;Zinabu and Pearce 2003), but no excessive concentrations have been reported (Tables 4 and 6). …”
Section: Mercurymentioning
confidence: 99%
“…Despite widespread awareness of potential healthrelated problems, the contaminant concentrations and distribution in Wsh from these lakes are not well studied, especially the potent human neurotoxin methylmercury, which normally constitutes at least 90% of the total mercury burden in Wsh (Bloom 1992). The most recent data obtained for other trace elements in waters of the EARV are, respectively, from the works of Cash et al (2003) and Zinabu and Pearce (2003) (Tables 5, 6).…”
Section: Health Related Issues In the Rift Valley Lakesmentioning
confidence: 99%